2014
DOI: 10.3766/jaaa.25.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Developmental Course of the Acoustic Properties of the Human Outer and Middle Ear Over the First 6 Months of Life by Using a Longitudinal Analysis of Power Reflectance at Ambient Pressure

Abstract: The overall maturation of the middle ear can result in a lower reflectance at higher frequencies and a higher reflectance at lower frequencies. This could be explained by known changes in ear-canal and/or middle-ear structures across this time period, which could lead to changes in mass and resistance. An increase in volume in the middle-ear cavity, reduction of middle-ear debris, and overall decrease in resistive elements might be contributing to these changes. Significant differences were observed between ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
4
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 47 publications
(135 reference statements)
4
58
4
1
Order By: Relevance
“…The largest changes in ambient energy reflectance in infants relative to adults occur below 0.5 kHz and above 2 kHz between 1 and 6 months of age (Aithal, Kei, & Driscoll, 2014; Keefe, Bulen, Arehart, & Burns, 1993; Shahnaz, Cai and Qi, 2014). There is up to a 30% change in mean energy reflectance and admittance magnitude from 0.25 - 0.75 kHz between 4 and 24 weeks of age (Sanford and Feeney, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The largest changes in ambient energy reflectance in infants relative to adults occur below 0.5 kHz and above 2 kHz between 1 and 6 months of age (Aithal, Kei, & Driscoll, 2014; Keefe, Bulen, Arehart, & Burns, 1993; Shahnaz, Cai and Qi, 2014). There is up to a 30% change in mean energy reflectance and admittance magnitude from 0.25 - 0.75 kHz between 4 and 24 weeks of age (Sanford and Feeney, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating test-retest reliability of WBA in infants have reported good reliability (Hunter et al, 2008a;Shahnaz et al, 2014;. In the study by Vander Werff et al They also found that the reliability results were equivalent irrespective of the type of stimuli (broadband chirps and specific sine waves) used for the WBA measure.…”
Section: Reliability Of Wbamentioning
confidence: 97%
“…Hunter et al and Merchant et al suggested that the reason they did not find developmental changes compared to other studies could be partly attributed to methodological differences including the age of subjects and differences in the equipment and probe tips. and In a recent study, Shahnaz, Cai and Qi (2014) established normative WBA data in infants from birth to six months of age (Figure 1.5). Using a longitudinal paradigm, they also studied the time course and rate at which functional maturation of the middle ear occurs in 18 infants from birth through to six months of age.…”
Section: Developmental Trends In Wbamentioning
confidence: 99%
See 2 more Smart Citations